Children's reception of critical concepts in animated movies. (August 2022) - Alehpour, Mania; Abdollahyan, Hamid
The purpose of this study is to reveal how children interpret animated movies that include critical concepts. The study investigates the mechanism of 20 Iranian children's interpretation aged 9–12 of animations that contain critical concepts and challenging ideas. Participants were interviewed by an ethnographic approach immediately after watching three animated movies, Zootopia, Kung Fu Panda 3, and Inside Out. The collected data were interpreted based on reception theory, sociocultural theory, and frame theory. Three categorizations emerged from the data collected from interviews with children: framegroup, different framegroup, and incomplete framegroup. The variables most influencing children's interpretation of animations were their schemas or frames and the conceptual tools to interpret the animated movies. Some of the results show that the selected animations were not influential enough to change children's schemas and improve their critical thinking. However, if they were equipped with critical conceptual tools, they would grasp and interpret critical concepts featured in the animations.